Cooperation in renewable energy: the challenge of Brazil and India in the multi-polarized world. - Mousinho, Maria Cândida Arrais de Miranda (2018)
The search for an understanding of the phenomena or for the challenges related to the contemporary world can not follow a systematic, productive and coherent path if we do not take into account the States whose actions can have global implications. This is the case of Brazil and India, key nations for the understanding of the global structures of production and consumption of energy. Facing the challenges of increasing energy demand, environmental issues related to CO2 emissions, the need to diversify the energy matrix of these two countries, the emergence of the countries of the South in the global political and economic scenario – turning the international arena into a multi-polarized environment - cooperation in renewable energy rises as an element that can help Brazil and India overcome these challenges. Particularly since the 2000s, Brazil and India have shown interest in cooperating in the field of renewable energy. However, the data found showed that this cooperation is still considered incipient. In this context, the overall objective of this work was to propose strategies to expand such cooperation. Thus, it was necessary to learn about the energy profiles of the two countries under study and to contextualize Brazil and India in the area of energy cooperation, verifying documents that proved the official interest of both countries in cooperating in this area. In addition, the main renewable energy policies established by the two countries were identified in order to know the types of renewable sources in which they have been developing their policies. The scientific and technological data-mapping of both countries was also carried out to learn the types of renewable energy on which they focus their scientific and technological production and verify existing partnerships in scientific production established by Brazil and India. This has helped to identify in which type of renewable energy these countries hold expertise or interests. In order to identify elements that may limit or promote cooperation in renewable energy between the two countries, a questionnaire was applied with officials from the foreign ministries of the two countries and interviews were conducted with professionals working in the area studied. The results obtained made it possible to propose strategies that could help to promote cooperation between the two states in the field of renewable energy, either through the scientific and technological via or through the strengthening of the political dialogue in the field of renewable energy between the concerned ministries of each of these countries. Solar energy and biofuels are presented as sources with greater possibility of cooperation between the two States under study.